Implementation of the Poor Community Empowerment Policy (A Study on the Family Hope Program in Palembang City) - Deffi Haryani (Universitas Sebelas Maret, 2021)
This research describes and analyzes the factors causing the ineffective implementation of the empowerment policy for the poor, through the process of implementing the “Family Hope Program”. This research was conducted in Palembang City. The research method used in this study was a qualitative method, because the researchers themselves were directly involved in the research process, including serving as the participant of observation. The research design used was